Predictive factors for survival outcomes of high- risk febrile neutropenic patients: A 3-year study at a single center in Thailand - Wannaphorn Rotchanapanya (2020)
© 2019, Siriraj Medical Journal. Objective: This study aimed to identify the risk factors associated with mortality in febrile neutropenic patients. Materials and Methods: This 3-year, single center, retrospective, observational study was conducted at Chiangrai Prachanukroh Hospital, Chiangrai Province, Thailand. The inclusion criteria consisted of a patient age of over 15 years and a diagnosis of febrile neutropenia. Results: Most of the 303 febrile neutropenic inpatients had a Multinational Association for Supportive Care in Cancer (MASCC) risk score < 21. The median length of stay was 6 days (interquartile range: 4-11 days). During 30 days of admission, 24.8% of the patients succumbed. In a univariate analysis, patients receiving G-CSF, the postchemotherapy- related group, patients with MASCC score > 16, and patients admitted in private had significantly higher survival rate. In a multivariate analysis, a MASCC score ≤ 16 and non-chemotherapy-related groups were associated with an increased mortality risk. Conclusion: The 30-day survival rate of febrile neutropenic patients in Thailand is seventy-five percent. Low MASCC score and non-chemotherapy-related neutropenia are associated with a higher risk of unfavorable outcomes.